Application of liquid film dielectric barrier discharge plasma reactor in the degradation of rhodamine B: Performance optimization, mechanism and pathways. (December 2022) - Zhao, Lixian; Sun, Yabing; Qiu, Rui; Sun, Hao; Feng, Jingwei
Abstract: In the present work, the degradation pathways and mechanism of rhodamine B (RhB) using a novel liquid film dielectric barrier discharge (DBD) plasma reactor were examined. Moreover, the optimization of the performance of DBD was discussed. The results showed that the atmosphere of the discharge area and the input power had a significant effect on the removal of RhB. After 21 min of treatment using DBD plasma system, about 90.2 % of RhB was degraded under the following experimental conditions: initial RhB concentration of 40 mg/L; input power of 125 W and initial pH of 6.78. The use of free radical scavengers proved that hydroxyl radicals played a key role in the degradation of RhB. In addition, the degradation intermediates of RhB were identified using liquid chromatography mass spectrometry, and possible degradation pathways were proposed. During the degradation of RhB, with the extension of treatment time, the values of COD, BOD5 and TOC decreased. After the treatment using DBD plasma, the BOD5 /COD of RhB solution increased from 0.0326 to 0.3867, and the biodegradability was also observed to have greatly improved. The potential toxicity was predicted by US-EPA-TEST software. Graphical abstract: Unlabelled Image Highlights: RhB elimination using a new type of liquid film DBD reactor was investigated. Various parameters on RhB degradation were studied. H2 O2, O3, OH and O2 − participation in the RhB degradation. Degradation pathways and mechanism of RhB were proposed.